Corrosion behavior of novel titanium-based composite with engineering 3D artificial nacre-like structures. (January 2023) - Lu, Y.J.; Liu, X.C.; Liu, Y.J.; Wu, X.; Jiang, Y.; Liu, Z.; Lin, J.X.; Zhang, L.C.
Graphical abstract: Abstract: Metallic composites with engineering 3D bioinspired architectures are difficult to construct by traditional processing methods. Inspired by nacre structure, a novel titanium-based composite (TCCP) with engineering 3D artificial nacre-like structures consisting of commercial purity titanium (CPTi, served as brick) and Ti6Al4V (TC4, served as mud) were firstly produced by coupling selective laser melting (SLM) and hot isostatic pressing (HIP). To determine the introduction of "brick-mud" interfaces potentially whether would change the corrosion behavior of the alloy, electrochemical tests were used to express the corrosion mechanism of the TCCP. The outcomes indicated that this composite structural material also exhibits excellent corrosion resistance, which was superior to the HIP treated SLM-TC4 and close to the HIP-produced CPTi. Moreover, a continuous passive film could form on the interface between the CPTi-brick and TC4-mud region in the TCCP matrix. The study is expected to provide new insight into designing artificial nacre-like composite alloys.